Pengaruh Independensi, Locus of Control dan Motivasi Kerja Pada Kinerja Auditor di Kantor Akuntan Publik Provinsi Bali - Charnia Dewi, Ni Made Elvin; Suardikha, I Made Sadha (E-Jurnal Akuntansi; Vol 27 No 2 (2019)DO - 10.24843/EJA.2019.v27.i02.p01, 2019)
The purpose of this study was to determine the effect of independence, locus of control, and work motivation on auditor performance. The location of this research is at the Public Accountant Office (KAP) of the Province of Bali. The population in this study were all   auditors working at the Bali Provincial Public Accountant Office. The results of this study   indicate that independence, locus of control and work motivation have a positive effect on   auditor performance. Independence variables, locus of control and work motivation have an effect on auditor performance by 78 percent, while 21.8 percent is influenced by other variables outside the research model. Based on the results of this study, the public acountant office should maintain an attitude of independence, locus of control and work  motivation amongst their auditors, in order for them to carry out his/her duties and be   more honest and responsible in working. Keywords : independence, locus of control, work motivation and auditor performance